2009
DOI: 10.1159/000191203
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Alzheimer’s Disease in the Uppsala Longitudinal Study of Adult Men

Abstract: Background/Aims: Genetic factors influencing common complex conditions have proven difficult to identify, and data from numerous investigations have provided incomplete conclusions as to the identity of these genes. Here we aimed to identify susceptibility genes for late-onset Alzheimer’s disease (AD). Methods: The case-control analysis included samples from 86 AD patients and 404 cognitively healthy controls selected from the Uppsala Longitudinal Study of Adult Men (ULSAM). In the incidence analysis, all 1,08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 72 publications
1
59
0
Order By: Relevance
“…Thus, 118 publications were futher excluded. Finally, 10 eligible studies [16,19,[21][22][23][24][25][26][27][28] were recognized in this meta-analysis. The main characteristics of all these studies are listed in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 118 publications were futher excluded. Finally, 10 eligible studies [16,19,[21][22][23][24][25][26][27][28] were recognized in this meta-analysis. The main characteristics of all these studies are listed in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Several studies [16,19,[21][22][23][24][25][26][27][28] tried to find out any association between MTHFR A1298C polymorphism and the risk of AD; due to different populations, case selections, and sample sizes, the association remained inconclusive. Two articles [16,25] revealed the genetic association of MTHFR A1298C polymorphism with AD risk, but others indicated lack of this association.…”
Section: Introductionmentioning
confidence: 99%
“…Other case-control studies have found no significant associations [12][13][14], although the small sample sizes in several cases meant a lack of statistical power.…”
Section: Ryan 10mentioning
confidence: 85%
“…Of the few prior case-control studies which have examined ESR2 polymorphisms [13,21,29,42,43], rs4986938 is the only one common to multiple studies. In keeping with our findings, they report no independent association between AD prevalence and rs4986938.…”
Section: Ryan 11mentioning
confidence: 99%
See 1 more Smart Citation